The Roles of Respectful Leadership and Overqualified Employees on Knowledge Sharing and Knowledge Hiding - Hardi, Hardi; Alviani, Devi; Dewi, Puspa; Astarina, Ivalaina; Fitrio, Tomy (Jurnal Aplikasi Manajemen, 2024)
In response to the competitive and dynamic business environment, understanding the determinants of knowledge sharing and knowledge-hiding behavior is crucial for optimizing knowledge utilization in achieving sustainable competitive advantage. This study aimed to develop a conceptual model of the relationships between overqualified employees, knowledge sharing, knowledge hiding, and respectful leadership. Data were collected from 94 BUMN Bank employees, and data were processed using PLS Structural Equation Modeling (SEM). This study proposes respectful leadership as a strategy to increase knowledge-sharing behavior and reduce knowledge-hiding behavior. The results of this study show that overqualified employees have an effect on knowledge sharing and knowledge hiding. Then, respectful leadership strengthens the effect of overqualified employees on knowledge sharing but weakens the effect of overqualified employees on knowledge hiding. The results of this study strengthen social exchange theory, where a respected leader will make individuals more concerned with social exchange than economic exchange so they don't hide information.